2017
DOI: 10.1186/s12967-017-1152-5
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Toll-like receptor 9 signaling in B cell malignancies and its potential therapeutic application

Abstract: Toll-like receptor 9 (TLR9) is expressed in a variety of B-cell malignancies and works as a bridge between innate and adaptive immunity. CpG oligodeoxynucleotides (CpG ODNs), TLR9 agonists, are able to induce anticancer immune responses and exert direct effects against cancer cells, serving as cancer therapeutic agents. Therefore, TLR9 might be a potential therapeutic target for drug development. However, several new evidences have revealed that direct effects of TLR9 agonists on B-cell malignancies is controv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 94 publications
(100 reference statements)
1
14
0
Order By: Relevance
“…S7A and S7B). These results paralleled the response for the activation of TLR9-dependent pathways (33,34). NETs significantly enhanced TLR9 expression together with an increase in the phosphorylation of NFkB, MAPK/p38, and STAT3 in SU-DHL2 cells (Fig.…”
Section: Nets Promoted Proliferation and Migration Through The Activasupporting
confidence: 76%
See 1 more Smart Citation
“…S7A and S7B). These results paralleled the response for the activation of TLR9-dependent pathways (33,34). NETs significantly enhanced TLR9 expression together with an increase in the phosphorylation of NFkB, MAPK/p38, and STAT3 in SU-DHL2 cells (Fig.…”
Section: Nets Promoted Proliferation and Migration Through The Activasupporting
confidence: 76%
“…TLR9 was mainly expressed in immune cells including B cells, dendritic cells, and macrophages, and it acts as a bridge between innate and adaptive immunity in the antitumor responses in solid tumors (38). But in DLBCL, tumor cells can express TLR9 and directly response to the activation of TLR9 (32), and increasing evidence has shown that TLR9 expression on DLBCL exhibits high heterogeneity and the activation of TLR9 in normal or tumor B cells elicits the opposite biological effects (34). James and colleagues found that inhibiting TLR9 in normal B cells could increase accumulation of MYD88 L265P plasmablasts and may impair B-cell malignancies treatment (39).…”
Section: Discussionmentioning
confidence: 99%
“…Unmethylated cytosine-guanine dinucleotide-containing oligodeoxynucleotide, as an agonist of Toll-like receptor 9 (TLR9), activates immune responses for use as vaccines to treat cancer, infectious diseases, and allergies (Bai et al., 2017 ). The obstacles in clinical application of CpG are the degradation by DNase in physiological conditions and low uptake efficiency by cells.…”
Section: Applications Of Dna Tetrahedron In the Field Of Drug Deliverymentioning
confidence: 99%
“…These results may support the hypothesis that CpG stimulates TLR9 expression in CD19-positive B cells and thus leads to systemic antitumor adaptive immunity. 25 …”
Section: Discussionmentioning
confidence: 99%